2009
DOI: 10.1364/oe.17.005743
|View full text |Cite
|
Sign up to set email alerts
|

Optical guiding of absorbing nanoclusters in air

Abstract: Two effects of the light-matter interaction are widely used for micromanipulation of particles with laser beams [1]: radiation pressure [2], originating from a direct transfer of momentum from photons, and electric dipole (gradient) force acting on polarized particles [3]. In gaseous media, however, the heating of absorbing particles by light leads to much stronger radiometric forces [4] considered until now only as an obstacle which prevents a stable trapping [5]. In contrast, here we show that photophoretic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
146
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(154 citation statements)
references
References 88 publications
5
146
2
1
Order By: Relevance
“…Raman spectroscopy combined with rapid methods for trapping particles [63] is one of the promising techniques to explore. In this work, we have combined photophoretic [44,48,51,52,63] trapping and Raman spectroscopy to characterize single bioaerosol particles in air. In particular, a single light absorbing pollen or fungal spore is trapped in air by photophoretic forces, and Raman spectroscopy is used as an interrogator, to form photophoretic trapping Raman spectroscopy (PTRS).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raman spectroscopy combined with rapid methods for trapping particles [63] is one of the promising techniques to explore. In this work, we have combined photophoretic [44,48,51,52,63] trapping and Raman spectroscopy to characterize single bioaerosol particles in air. In particular, a single light absorbing pollen or fungal spore is trapped in air by photophoretic forces, and Raman spectroscopy is used as an interrogator, to form photophoretic trapping Raman spectroscopy (PTRS).…”
Section: Discussionmentioning
confidence: 99%
“…The relative strength of these forces depends on the absorptivity of the particle, the thermal conductivity of the particle, and the particle morphology, on the pressure and thermal conductivity of the surrounding gas, and on the strength and geometry of the optical field. Previous studies found that for strongly absorbing particles such as carbon nanofoam, the photophoretic force can be orders of magnitude stronger than the radiative force [48]. We performed an initial estimation assuming homogenous spherical particles illuminated by a plane wave using the approximations and derivations in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absorbing (i.e. non-transparent) particles in liquids and gaseous medium are also repelled and pushed away from intensity maxima [37][38][39] . In addition, a dark trap is more beneficial for some applications than a bright trap for a simple reason: the light may not interact with the trapped object.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been introduced to capture transparent solid glass microspheres by a pair of counterpropagating moderately focused Gaussian beams 19,20 . Counterpropagating schemes with high-order optical modes such as Laguerre-Gaussian beams have also been proposed for trapping and manipulation of absorbing particles 21,22 . Here we consider both options by using circularly polarized light beams with identical helicity, power and bell-or doughnut-shaped transverse intensity profiles.…”
Section: Chiral Light Fieldmentioning
confidence: 99%